2020
DOI: 10.1016/j.btre.2020.e00504
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the effect of different microwave extraction parameters on the recovery of polyphenols from shiitake mushrooms: Comparison with hot-water and organic-solvent extractions

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 36 publications
(76 reference statements)
0
20
0
Order By: Relevance
“…The extraction time in MAE represents the time length the sample is exposed to microwave irradiation. In a long extraction time, the sample is exposed to microwave irradiation longer which causes more ruptures in sample tissues and plant cell walls leading to an increase in phenolics released [ 30 ]. Hence, the extraction yield of the phenolics and antioxidant properties increased in response to increasing the extraction time.…”
Section: Resultsmentioning
confidence: 99%
“…The extraction time in MAE represents the time length the sample is exposed to microwave irradiation. In a long extraction time, the sample is exposed to microwave irradiation longer which causes more ruptures in sample tissues and plant cell walls leading to an increase in phenolics released [ 30 ]. Hence, the extraction yield of the phenolics and antioxidant properties increased in response to increasing the extraction time.…”
Section: Resultsmentioning
confidence: 99%
“…When increasing microwave power with increasing extraction temperature, that was resulted to destroy the thermal sensible active compounds such as caffeic acid, ferulic acid. [ 10 11 ]…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, heating of the water molecules inside the plant matrix expands cellular materials and facilitates the release of the cell contents when the structure is broken (Maroun et al, 2018). MWs have been widely used to extract various phytochemicals, such as tannins, alkaloids, and saponins, from different plant sources (Xiaokang et al, 2020). Dalmoro et al (2018) showed that MW pretreatment (60−75 • C 1000 W, 2.45 GHz, 1 min) reduced the tannin content with minimum impact on the structure of legume seeds.…”
Section: Removal Of Antinutritional and Antitechnological Factorsmentioning
confidence: 99%